Preliminary phytochemical screening and antimicrobial activity of fresh plant extract of Indian folk medicinal plant, Gnaphalium polycaulon - Shanmugapriya Kaminidevi; Thayumanavan Thangavelu; Alamelu Lakshmanan; Divya Gunashekar; Hilda Thomas Chirayil; Jamuna Karanangattil Sukumaran; Srija Murugan (International Journal of Phytomedicine, 2014)
Nature has been a source of medicinal agents for thousands of years. Plants produce a diverse array of bioactive molecules, making them a rich source of diverse type of medicines. Thus, natural products with pharmacological or biological activities still play a very important role in medicine. The objective of the present study deals with the exploration of specific species of medicinal plants found in Western Ghats, India and was to investigate the presence of phytochemicals constituents and to determine antimicrobial analysis of the Gnaphalium polycaulon in hexane solvents. Fresh G. polycaulon was air dried and coarsely powdered. Then all the extracts obtained were subjected for phytochemical screening using standard procedure. Bacterial and fungal cultures were used for screening antimicrobial study by agar well diffusion method. It reported the presence of major phytochemicals in all solvent extracts. The phytochemical of the plant extract showed that the leaf and stem were rich in major phytochemicals such as alkaloids, flavonoids, tannins and saponins, than flower extract. The resource base of the traditional folk medical practices is more prevalent in rural and tribal villages of India. Our findings provided evidence that crude hexane extracts of selected plants contain medicinally important bioactive compounds and their use in the traditional folk medicines practices.